2022
DOI: 10.1101/2022.08.18.22278938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First detection of Monkeypox virus genome in sewersheds in France

Abstract: A monkeypox virus outbreak is currently spreading in multiple non-endemic countries since May 2022. The atypical clinical profile of patients has led to a very likely underestimation of the number of cases at the beginning of epidemic. The detection and quantification of the Monkeypox virus genome in sewersheds in Paris (France) correlated temporally with the identification of the first case of infection and the spread of the disease within the population connected to the sewage system.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…This is an alternative pathway for the production of EEV. It has been reported that the virion morphogenesis process in the prototype VACV can go awry, leading to the formation of dense particles that are not infectious [121]. However, this behavior has not been observed in MPXV [122].…”
Section: Genome Organization Replication Cycle and Morphologymentioning
confidence: 99%
“…This is an alternative pathway for the production of EEV. It has been reported that the virion morphogenesis process in the prototype VACV can go awry, leading to the formation of dense particles that are not infectious [121]. However, this behavior has not been observed in MPXV [122].…”
Section: Genome Organization Replication Cycle and Morphologymentioning
confidence: 99%